The Role of Human Beings in Maintaining Environmental Harmony According to Sayyed Hossein Nasr: An Analytical Study from the Perspective of Ziauddin Sardar's Ecological Theory - Muhammad Mufti Faiq Kamal; Usman Syihab (Al-Zahra : Journal for Islamic and Arabic Studies, 2026)
This study aims to analyze the human role in maintaining environmental harmony from the perspective of Seyyed Hossein Nasr. The study is motivated by the escalating environmental crisis in Indonesia and Southeast Asia, the widening gap between technical solutions and the spiritual dimensions of environmental degradation, and the need to incorporate a comprehensive Islamic philosophical perspective into contemporary environmental discourse. The novelty of this research lies in its analysis of human existence as khalīfah (vicegerent) on earth within Nasr's thought and its relevance to the Sustainable Development Goals (SDGs). This research employs a library-based qualitative approach with a descriptive-analytical method through content analysis of Seyyed Hossein Nasr's primary works, supported by Qur'anic exegesis, Islamic philosophical literature, and contemporary environmental studies, while adopting Ziauddin Sardar's framework of environmental ethics. The findings reveal that the root cause of the environmental crisis lies in the loss of the sacred perception of nature and the dominance of a materialistic worldview that disrupts cosmic balance. According to Nasr, nature is a manifestation of divine signs, and human beings, as khalīfah, bear the responsibility of preserving and maintaining its harmony. Therefore, addressing the environmental crisis requires the reconstruction of spiritual consciousness through the reaffirmation of the principle of tawḥīd and the integration of scientific knowledge with ethical values to foster a harmonious relationship between humanity and nature.